The Role of PEG on Pd- and Cu-Catalyzed Cross-Coupling Reactions - Pires, Marina J. D.; Purificação, Sara I.; Santos, A. Sofia; Marques, M. Manuel B. (Synthesis, 2017)
Carbon–carbon and carbon–heteroatom coupling reactions are among the most important transformations in organic synthesis as they enable complex structures to be formed from readily available compounds under different routes and conditions. Several metal-catalyzed cross-coupling reactions have been developed creating many efficient methods accessible for the direct formation of new bonds between differently hybridized carbon atoms.During the last decade, much effort has been devoted towards improvement of the sustainability of these reactions, such as catalyst recovery and atom efficiency. Polyethylene glycol (PEG) can be used as a medium, as solid-liquid phase transfer catalyst, or even as a polymer support. PEG has been investigated in a wide variety of cross-coupling reactions either as an alternative solvent to the common organic solvents or as a support for catalyst, substrate, and ligand. In this review we will summarize the different roles of PEG in palladium- and copper-catalyzed cross-coupling reactions, with the focus on Heck, Suzuki–Miyaura, Sonogashira, Buchwald–Hartwig, Stille, Fukuyama, and homocoupling reactions. We will highlight the role of PEG, the preparation of PEGylated catalysts and substrates, and the importance for the reaction outcome and applicability.1 Introduction2 PEG in Heck Reactions3 PEG in Homocoupling Reactions4 PEG in Suzuki–Miyaura Reactions5 PEG in Sonogashira Reactions6 PEG in Buchwald–Hartwig Reactions7 PEG in Stille Reactions8 PEG in Fukuyama Reactions9 PEG in Miscellaneous Cross-Coupling Routes10 Conclusions
Keywords: cross-coupling reaction; palladium; copper; poly(ethylene glycol); PEG; solvent